0289 Preventing needlesticks and other sharps injuries to home care aides: results of a survey to identify hazards during home visits0289 Preventing needlesticks and other sharps injuries to home care aides: results of a survey to identify hazards during home visits. (23rd June 2014) - Kriebel, David; Brouillette, Natalie; Markkanen, Pia; Galligan, Catherine; Sama, Susan; Gore, Rebecca; Laramie, Angela; Okyere, Daniel; Sun, Chuan; Davis, Letitia; Quinn, Margaret
Abstract : Objectives: To follow up on our previous finding that home care (HC) aides have a substantial risk of injury with used sharp medical devices, this study's goal was to identify modifiable aspects of aide-client encounters during HC visits that increase risk of sharps injuries (SI). Method: A survey of 1249 HC aides was conducted in eastern Massachusetts. Approximately half the participants (634) were employed by HC agencies, and half (615) directly by HC clients and their families. A questionnaire gathered data on aides' most recent home visits, enabling quantification of hazardous working conditions. The specific investigation described here focused on understanding determinants of hazardous conditions likely to increase the risk of SI including: the aide finding used sharps lying around the house; assisting a client with using a sharp; and disposing of sharps. Poisson regression modelling was used to identify important predictors of handling or encountering used sharps. By linking these results to national data on HC visits and clients, we estimated the frequency with which these hazardous conditions occur to HC aides nationwide. Results: Although not authorised to do so, 7% of aides assisted clients to use a sharp. Aides were much more likely to encounter sharps if they were employed directly by clients/families than if employed through an agency. Other important determinants of sharps exposure included client medical conditions like diabetes, and aide characteristics including professional certification. Conclusions: The results are being investigated further through focus groups of HC aides and used to develop preventive interventions.